A STUDY ON RESILIENCE AND SELF EFFICACY AMONG THE HIGHER EDUCATION STUDENTS OF WEST BENGAL - Ansary, Majaffar (AGPE THE ROYAL GONDWANA RESEARCH JOURNAL OF HISTORY, SCIENCE, ECONOMIC, POLITICAL AND SOCIAL SCIENCE, 2023)
Resilience and Self-efficacy are two important terms in education and psychology. The dictionary meaning of the word resilience is ‘the capacity to recover quickly from difficulties; toughness’. Another side the word self-efficacy means ‘an individual’s belief in his or her capacity to execute behaviors necessary to produce specific performance attainments’ (Bandura, 1977, 1986, 1997). The concept of self-efficacy was 1st proposed by Albert Bandura. Self-efficacy and Resilience both are very important to everyone’s life because self-efficacy plays a vital role for developing a good personality and resilience gives individuals strength to overcome any difficulties and adversities. Resilience and Self-efficacy both, differs from person to person, genders, ethnicities, races and communities. Students of different strata of the society always experience various types of difficulties and distresses in achieving their academic and also non-academic successes in both personal as well as professional life. Basically, it is very common in higher education level. This stage is very crucial for the students. Research shows that ‘those who are more Resilient have the "ability to adjust and adapt to the changes, demands, and disappointments that come up in the course of life" (Joseph, 1994, p. xi). Resilient students have the capacity to overcome personal weaknesses and negative environmental conditions—they have the ability to succeed under adverse conditions. This paper tried to find out the level of resilience and the level of self-efficacy among the higher education students of West Bengal. It also explored the importance of resilience and self-efficacy in every day’s life specially for the students of higher education.